Harmonisasi Moderasi Beragama antara Hukum Islam dan Hak Asasi Manusia: Pendekatan Maqāṣid al-Syarī‘ah di Negara Plural - Haswin, Ferry Harry (CV Global Research Publication, 2026)
The relationship between Islamic law and human rights has often been perceived as dichotomous, particularly in the context of religious freedom and plural societies. This study aims to analyze the harmonization of religious moderation between Islamic law and human rights through the approach of maqāṣid al-sharī‘ah. This research employs a qualitative method with normative and conceptual approaches through an examination of classical Islamic legal principles and the framework of modern human rights. The findings indicate that the apparent tension between Islamic law and human rights does not constitute an absolute contradiction, but is largely influenced by rigid textual interpretations and incompatibility with social contexts. The framework of maqāṣid al-sharī‘ah offers a mediative paradigm by placing public welfare (maṣlaḥah) and the protection of fundamental human rights as top priorities. This study proposes a conceptual model of harmonization based on reinterpretation, contextualization, and value integration that is relevant to be implemented in plural states such as Indonesia. The novelty of this research lies in its integrative approach that bridges normative Islamic jurisprudence with universal human rights principles through a moderation framework based on maqāṣid.